A phase III, open-label, randomised multicentre study to evaluate the immunogenicity and safety of a booster dose of two different reduced antigen diphtheria-tetanus-acellular pertussis-polio vaccines, when co-administered with measles-mumps-rubella vaccine in 3 and 4-year-old healthy children in the UK. Issue 17 (19th April 2018) - Marlow, Robin; Kuriyakose, Sherine; Mesaros, Narcisa; Han, Htay Htay; Tomlinson, Richard; Faust, Saul N.; Snape, Matthew D.; Pollard, Andrew J.; Finn, Adam
Highlights: We assessed immunogenicity and safety of dTpa-IPV booster vaccine in 3–4 years olds. The immunogenicity of dTpa-IPV (Boostrix-IPV) was non-inferior to Repevax. Both vaccines were co-administered with mumps-measles-rubella vaccine. Both vaccines had clinically acceptable safety and reactogenicity profiles. Abstract: Aim: To evaluate the immunogenicity and safety of a reduced antigen diphtheria-tetanus-acellular pertussis-inactivated poliovirus (dTap-IPVB ) vaccine ( Boostrix-IPV, GSK) as a pre-school booster in 3–4 year old children as compared to dTap-IPVR ( Repevax, Sanofi Pasteur), when co-administered with mumps-measles-rubella vaccine (MMRV). Methods: This phase III, open label, randomised study was conducted in the UK between April 2011 and April 2012. Children due their pre-school dTap-IPV booster vaccination were randomised 2:1 to receive one of two different dTap-IPV vaccines (dTap-IPVB or dTap-IPVR ) with blood sample for immunogenicity assessment just prior and one month after vaccination. Immune responses to diphtheria, tetanus and polio antigens were compared between the study vaccines (inferential comparison). In the absence of an accepted pertussis correlate of protection, the immunogenicity of dTap-IPVB vaccine against pertussis was compared with historical pertussis efficacy data (inferential comparison). Safety and reactogenicity of both study vaccines were evaluated. Results: 387 children were randomised and 385 vaccinated: 255 in the dTap-IPVB group and 130 in the dTap-IPVR group. Prior to vaccination, ≥76.8% of children had anti-diphtheria and ≥65.5% had anti-tetanus titres above the protection threshold; for pertussis, the pre-vaccination seropositivity rate ranged between 18.1 and 70.6%. Both vaccines were immunogenic with 99.2–100% of children achieving titres above the pre-specified seroprotection/seropositivity thresholds. One serious adverse event not considered as causally related to the study vaccination by the study investigator was reported in the dTap-IPVB group. Conclusion: Non-inferiority of dTap-IPVB to dTap-IPVR was demonstrated. Both vaccines had a clinically acceptable safety and reactogenicity profile when co-administered with MMRV to children 3–4 years old. Trial registration: NCT01245049 (ClinicalTrials.gov )